Pemberdayaan Kelompok Usaha Mikro Donat Kentang Aneka Toping Studi kasus Kelompok Usaha Mikro Donat Kentang di kecamatan pakal dan kecamatan Karang pilang Surabaya - Mulus Sugiharto (UII, 2018)
Most of the various toping donuts are still using manual systems to make donuts, by hand, so the production capacity is relatively low. Management problems encountered include not yet implementing marketing management professionally, and not yet have Licensing Household Industry (PIRT). To overcome these problems, through this program of dedication to the community, given the solution 1) to provide aid in the production of potato-making machine by applying Appropriate Technology to improve productivity. And 2) to provide marketing management training so that they have knowledge about good marketing management . After training and production facilities are available, there is an increase in the number of productions and the quality of various Toping Potato Donuts and also affect their welfare level. The existence of this potato donut machine can increase productivity 3 times.